Ruangan Kelas dan Laboratorium Pintar (Menuju Smart Campus dengan Internet of Things) - Rahmat Fanshuri -; Wiwik Wiharti -; Firdaus - -; Ihsan Lumasa Rimra (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
Smart Classroom and Laboratory (SCL) is one of technologies that can be implemented to empower the availability of Information and Communication Technologies (ICT) infrastructure. All devices and components in class and labor will become entities that are integrated and embedded into electronic devices in order to make them to behave as the Internet of Things (IoT). SCL is used to assist lecturers in monitoring and managing classrooms and laboratories in real time. Moreover, the classroom / laboratory will be smarter because the lighting and cooling systems are made to adapt according to the number of people in the room.